Surface display of sialyltransferase on the outer membrane of Escherichia coli and ClearColi - Song, Hyun-Woo; Yoo, Gu; Bong, Ji-Hong; Kang, Min-Jung; Lee, Seung Seo; Pyun, Jae-Chul (ELSEVIER SCIENCE INC, 2019)
alpha 2,3-Sialyltransferase from Pasteurella multocida (PmST1) is an enzyme that transfers a sialyl group of donor substrates to an acceptor substrate called N-acetyl-D-lactosamine (LacNAc). In this study PmST1 was expressed on the outer membrane of wildtype Escherichia coli (BL21) with lipopolysaccharide (LPS) and ClearColi with no LPS, and then the enzyme activity and expression level of PmST1 were compared. As the first step, the expression levels of PmST1 on the outer membranes of wildtype E. coli (BL21) and ClearColi were compared according to the IPTG induction time, and the absolute amount of surface-displayed PmST1 was calculated using densitometry of SDS-PAGE. As the next step, the influence of LPS on the PmST1 activity was estimated by analyzing Michaelis-Menten plot. The enzyme activity of PmST1 was analyzed by measuring the concentration of CMP, which was a by-product after the transfer of the sialyl group of donor compounds to the acceptor compounds. From a Michaelis-Menten plot, the enzyme activity of the surface-displayed PmST1 and the maximum rate (V-max) of ClearColi were higher than those of wildtype E. coli (BL21). However, the K M value, which represented the concentration of substrate to reach half the maximum rate (V-ma(x)), was similar for both enzymes. These results represented such a difference in enzyme activity was occurred from the interference of LPS on the mass transport of the donor and acceptor to PmST1 for the sialyl group transfer.
Keywords: CELL-SURFACE; PURIFICATION; SEPARATION; PEPTIDES